What's Alter Got to Do with It? A Consideration of Network Content and the Social Ties That Provide It. (September 2019) - Greenberg, Jason
The strength of weak ties is among the most important theories in the social sciences. One paradoxical element of the theory has been widely understood and valued—that weak ties connect disparate regions of social structure. Less appreciated, however, is the arguably more paradoxical implication that someone only weakly connected to another would provide value beyond that which is provided by the recipient's (ego's) strong ties. Once this paradoxical feature of the theory and associated empirical literatures is acknowledged, the interests of the resource provider (alter) demand consideration. To do so faithfully requires first, the concession that different types of content can be transmitted across ties (e.g., financial, informational, physical, social) and content varies in important ways that relate to alter's interests and concerns. This article considers social network content and the strength of ties that provide different forms of it. The case of startups is used as a fruitful strategic research site because of the varied resources required at various stages of the startup process. Novel insights are proposed concerning what content flows across different types of social relationships in the context of "nascent" entrepreneurship. Examples from other contexts such as job search are also discussed to exemplify scope. Importantly, this article takes the perspective of the resource provider, alter, and considers her concerns about trust, misuse, and unauthorized transfer in dyadic exchange. In the process, a second paradoxical feature of the theory is identified and theorized, which usefully reveals the boundaries of exchange.